Peritoneal dialysis in PICU in a tertiary care hospital -a one year analysis - Dr.Supriya.N; Dr.Manoj D.; Dr.Basavaraj G.V. (Pediatric Review: International Journal of Pediatric Research, 2018)
Background:Renal replacement therapy has as established role in the pediatric intensive care unit. Peritoneal dialysis (PD) has been successfully used as a therapy for Acute Kidney Injury (AKI) since 1946. It is a frequent choice for chronic dialysis support, especially in children. There has been shift in developed countries of using hemodialysis and hemofiltration for renal replacement therapy in AKI, though observational studies in children and systematic review in adults show no difference in mortality between PD and Hemodialysis and hemofiltration. Today acute PD is a modality most often used in the developed world where its simplicity, effectiveness, and low cost make it attractive.The role of peritoneal dialysis in PICU is not well defined, although it remains frequently used, especially in low-resource settings. Hence the present study was performed to describe the indications and outcome of patients on PD. Objectives: Peritoneal dialysis in PICU – Indications and outcome. Materials and methods:Study design- Retrospective study. Methods- All patients between the age group of 1 month to 15 years, admitted to PICU and requiring PD formed the study group. All details i.e demographic data, indications for PD, complications and outcome was entered in systematically designed proforma and analysed. Results:Total of 30 patients was included in the study group. Out of 30,21children less than 5years,6 patients were between 5 to 10 years and 3 patients were between 10 to 15 years.Acute kidney injury (AKI) was the most common indication for PD (46%), followed by metabolic acidosis (40%) and chronic kidney disease (10%). Out of 30 patients, 16 patients recovered, 8 patients succumbed to the illness and 6 patients were referred to higher centre for Hemodialysis.Catheter blockage was the most common complication followed by bleeding and peritonitis. Hyperglycaemia was the most common metabolic disturbance seen followed by hypokalaemia. Conclusion: PD is still one of the most commonly used renal replacement therapy in PICU in resource limited settings. AKI is the most common indication for PD followed by CKD and metabolic acidosis. Outcome of PD is better in infants than in other age group. Catheter blockage was the most common complication and hyperglycaemia was most common metabolic abnormality.